Low TGFβ1 expression prevents and high expression exacerbates diabetic nephropathy in mice - Hathaway, Catherine K. (Proc Natl Acad Sci U S A, 2015)
Nephropathy develops in many but not all patients with long-standing type 1 diabetes. Substantial efforts to identify genotypic differences explaining this differential susceptibility have been made, with limited success. Here, we show that the expression of the transforming growth factor β1 gene (Tgfb1) affects the development of diabetic nephropathy in mice. To do this we genetically varied Tgfb1 expression in five steps, 10%, 60%, 100%, 150%, and 300% of normal, in mice with type 1 diabetes caused by the Akita mutation in the insulin gene (Ins2(Akita)). Although plasma glucose levels were not affected by Tgfb1 genotype, many features of diabetic nephropathy (mesangial expansion, elevated plasma creatinine and urea, decreased creatinine clearance and albuminuria) were progressively ameliorated as Tgfb1 expression decreased and were progressively exacerbated when expression was increased. The diabetic 10% hypomorphs had comparable creatinine clearance and albumin excretion to wild-type mice and no harmful changes in renal morphology. The diabetic 300% hypermorphs had ∼1/3 the creatinine clearance of wild-type mice, >20× their albumin excretion, ∼3× thicker glomerular basement membranes and severe podocyte effacement, matching human diabetic nephropathy. Switching Tgfb1 expression from low to high in the tubules of the hypomorphs increased their albumin excretion more than 10-fold but creatinine clearance remained high. Switching Tgfb1 expression from low to high in the podocytes markedly decreased creatinine clearance, but minimally increased albumin excretion. Decreasing expression of Tgfb1 could be a promising option for preventing loss of renal function in diabetes.